2019
DOI: 10.1186/s12889-019-7269-0
|View full text |Cite
|
Sign up to set email alerts
|

The use of folic acid, iron salts and other vitamins by pregnant women in the 2015 Pelotas birth cohort: is there socioeconomic inequality?

Abstract: Background Many low- and middle-income countries recommend micronutrient supplements for pregnant women to improve their nutritional status, prevent possible deficiencies and avoid fetal healgth consequences. This study evaluated the influence of socioeconomic status on the use of folic acid, iron salts and other vitamins and minerals among pregnant women in the 2015 Pelotas Birth Cohort. Methods This population-based birth cohort study was carried out with 4270 women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 31 publications
0
15
1
5
Order By: Relevance
“…Primiparous women were found to be more adherent than nulliparous and multiparous with the uptake of all the medications studied. That multiparous women used less has been reported by Miranda et al Although these authors did not directly measure the adherence, this use could be extended, albeit cautiously to adherence. The reason for the poor adherence among multiparous women is that after a number of deliveries, mothers can afford some degree of laxity towards the babies they are carrying.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Primiparous women were found to be more adherent than nulliparous and multiparous with the uptake of all the medications studied. That multiparous women used less has been reported by Miranda et al Although these authors did not directly measure the adherence, this use could be extended, albeit cautiously to adherence. The reason for the poor adherence among multiparous women is that after a number of deliveries, mothers can afford some degree of laxity towards the babies they are carrying.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have indicated that regular intake of iron and folic acid improves the haemoglobin levels and iron stores of pregnant women . A recent report from Brazil suggests a socio‐economic inequality in the use of iron salts, folic acid and vitamins among mothers, where use of iron salts was associated with non‐whites, while use of folic acid and vitamins was linked to white and richer mothers . However, the adherence with routine haematinics among women in lower‐middle‐income countries (LMIC) has not been extensively reported.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of micronutrients and its deficiencies are commonly observed in women during pregnancy and supplements will be recommended to avoid the association of associated malabsorption diseases, high fertility rates, to avoid neural tube defects in the pregnancies, limited knowledge towards the intake of nutrition during pregnancy. [ 32 ] One of the possible factors might be socioeconomic differences of these study settings, ethnicity, and time phrase. Our study had performed when the pregnant women were at 20 weeks of gestation and Kassa et al .…”
Section: Discussionmentioning
confidence: 99%
“…The drugs were classified into pharmacological groups by the Anatomical Therapeutic Chemical (ATC) classification system [10] at levels 1 (anatomical group), 2 (therapeutic group), and 5 (chemical substance). In this paper, we do not consider the use of iron salts, folic acid, vitamins, and other minerals, because such supplements are routinely recommended to pregnant women and have been analyzed separately in another study [11]. The independent variables were the following: age (≤19, 20-29, 30-47 years), skin color (white, black, and mixed/other), education (0-4, 5-8, 9-11, and 12 or more years of schooling), current income in minimum wages considering the amount of R$ 788.00 (USD 200.00) as one wage in 2015 (≤1, from 1.1 to 3, from 3.1 to 6, from 6.1 to 10, and >10), parity (1, 2, 3, and 4 or more children), number of prenatal visits (less than 6 visits and 6 or more), marital status (with/without a partner), smoking during pregnancy (yes/no), number of chronic and/or acute health problems (none, 1, 2, 3, and 4 or more), hospitalization during pregnancy (yes/no), and trimester of onset of prenatal care (first, second, or third).…”
Section: Methodsmentioning
confidence: 99%